2022
DOI: 10.5195/ijms.2022.763
|View full text |Cite
|
Sign up to set email alerts
|

Comparative review of large animal models for suitability of proximal aortic endovascular repair

Abstract: Background The advent of TEVAR heralds a paradigm shift in treating descending aortopathies and is viewed as a potential option for ascending aortic dissection (AD) repair too. Currently, TEVAR’s usage for ascending aortopathies remains limited. Consequently, an urgent requirement exists to choose appropriate animal models to better contemporary understanding of endovascularly treating Type-A ADs. This review article provides a summary of current literature on this topic. Two broad sections are cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Srinivas et al presented a current literature summary on the use of animal models in the endovascular treatment of ascending aortic dissection. 17 An overview of twenty-three published papers revealed that porcine and ovine species are the most suitable animal models for the examination of endovascular stent-graft feasibility. Increasing rates of Vancomycin-Resistant Enterococci (VRE) infections have provided ideal conditions for this opportunistic pathogen to develop antibiotic resistance.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Srinivas et al presented a current literature summary on the use of animal models in the endovascular treatment of ascending aortic dissection. 17 An overview of twenty-three published papers revealed that porcine and ovine species are the most suitable animal models for the examination of endovascular stent-graft feasibility. Increasing rates of Vancomycin-Resistant Enterococci (VRE) infections have provided ideal conditions for this opportunistic pathogen to develop antibiotic resistance.…”
Section: Future Perspectivesmentioning
confidence: 99%